Severe Colitis with Portal Venous Gas Caused by Brachyspira pilosicoli Infection - Chatani, Motoharu (Intern Med, 2019)
We herein report a case of Brachyspira pilosicoli-caused severe colitis presenting with portal venous gas. A 75-year-old man was admitted because of a fever, severe abdominal pain and bloody diarrhea. He was negative for anti-HIV antibodies. He had been in close contact with a dog earlier. Abdominal computed tomography detected severe wall-thickening and fat-stranding of the entire colon accompanied by portal venous gas. A smear examination of his stool showed many Gram-negative spiral rods, suggesting intestinal spirochetosis. A polymerase chain reaction assay using stool samples detected an amplified band specific for B. pilosicoli. He responded well to antimicrobial agents including metronidazole.